K-SAN'S Legacy - Paulus, Kennedy; Saripin, Sofia Sarmimi; Jaskin, Anastasia; Mar, Norfatihah; KK Peter, Suntison (2014)
Nowadays, making a business in Malaysia is one of the main ways for people to generate income for their living in daily life. Especially in food industry business, it is more likely to be moving towards success, due to the reason that Malaysia people love to eat. At this point of view, we can see that many people are trying to involve themselves into food industry business as a way for to gain more profitable income. The reason why we choose K-SAN'S as our company name is because of the combination of the first letter of our member name, which is Kennedy as K, Sofia as S, Anastasia as A, Norfatihah as N, and Suntison as the last S. Our company main product is sweet 3. Sweet 3 is actually a pudding made up of three layer sweet. The upper layer of the pudding is curds powder, the middle layer is fresh combination of different fruits, and the lower layer is the sweet and delicious pudding. We also give the opportunity to our customers to choose two types of any flavoured and mix them together. Sweet 3 will be launched on 04 September 2014, and the location will be at basement floor, 1 Borneo shopping mall. 1 Borneo shopping mall is a happening place to hang out with friends and families, especially during the weekends and public holidays.